A Review paper on Influence of Incentive-Based Schemes on Credit Card Adoption in Delhi-NCR (Journal of Informatics Education and Research, 2025)
This ponder looks at the affect of cashback and rewards programs on credit card utilization within the Delhi NCR locale, utilizing information from 2023 and early 2024. A mixed-methods approach including overviews, interviews, and information analysis was utilized to survey how these motivating forces impact shopper behavior and investing designs. Discoveries demonstrate that cashback offers and rewards are noteworthy drivers of credit card appropriation and utilization, with outstanding varieties over distinctive statistic bunches. The think about gives profitable bits of knowledge for money related educate and policymakers pointing to improve credit card acknowledgment and advance dependable utilization in quickly growing urban centers like Delhi NCR.